(untitled) (Journal of Engineering, 2014)
The aim of research is to show the effect of Ferric Oxide (Fe2O3) on the electricity production and wastewater treatment, since 2.5% of Ferric Oxide (Fe2O3) (heated and non heated) nanoparticles has been used. Characterization of nanoparticles was done using X-ray Diffraction (XRD) and Scan Electron Microscopy (SEM). The influence of acidity was also studied on both wastewater treatmenton the Chemical Oxygen demand (COD) and Biological Oxygen Demand (BOD) and voltage output was studied. From the results, it was infused that the dosage of 0.025 g/l and an initial pH 7 were founded to be optimum for the effective degradation of effluents. The results concluded that the treatment of anaerobic sludge wastewater using Ferric Oxide (Fe2O3) in combination with microbialmfuel cell technology is an efficient method for the treatment of anaerobic sludge wastewater.